The Impact of Air Pollution on Attributable Risks and Economic Costs of Hospitalization for Mental Disorders - Ziting Wu; Xi Chen; Guoxing Li; Lin Tian; Zhan Wang; Xiuqin Xiong; Chuan Yang; Zijun Zhou; Xiaochuan Pan (Institute of Labor Economics (IZA), 2020)
This study aims to fill the gap in our understanding about exposure to particulate matters with diameter less than 2.5 μm (PM2.5) and attributable risks and economic costs of mental disorders (MDs). We identify the relationship between PM2.5 and risk of hospital admissions (HAs) for MDs in Beijing and measure the attributable risk and economic cost. We apply a generalized additive model (GAM) with controls for time trend, meteorological conditions, holidays and day of the week. Stratified analyses are performed by age, gender and season. We further estimate health and economic burden of HAs for MDs attributable to PM2.5. A total of 17,252 HAs for MDs are collected. We show that PM2.5 accounts for substantial morbidity and economic burden of MDs. Specifically, a 10 μg/m3 daily increase in PM2.5 is associated with a 3.55% increase in the risk of HAs for MDs, and the effect is more pronounced for older males in colder weather. According to the WHO's air quality guidelines, 15.12 percent of HAs and 16.19 percent of related medical expenses for MDs are respectively attributable to PM2.5.
Keywords: Q51; Q53; I24; I31; G11; G41; J24; 330; attributable risk; economic cost; hospital admissions; mental disorders; PM2.5